Faktor-faktor yang Berhubungan dengan Self-Care Management pada Pasien Penyakit Ginjal Kronik - Nirmala Bakri; Yuliana Syam; Suni Hariati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to summarize the factors related to self-care management in chronic kidney disease (CKD) patients. A literature search was conducted using six databases: Pubmed, Scopus, EBSCOhost, Wiley Online Library, Taylor & Francis, and Garuda. The keywords used were